[Re(CO)3Cl(C5H4ClP)2] and [Re(CO)2Cl(C5H4ClP)3]: synthesis and characterization of two novel rhenium(i) phosphinine complexes. Issue 17 (3rd February 2016) - Hollering, Manuela; Reithmeier, Richard O.; Meister, Simon; Herdtweck, Eberhardt; Kühn, Fritz E.; Rieger, Bernhard
Abstract : Two novel rhenium(i ) phosphinine complexes [Re(CO)3 Cl(η 1 -C5 H4 ClP)2 ] (1 ) and [Re(CO)2 Cl(η 1 -C5 H4 ClP)3 ] (2 ) were synthesized and the molecular structure of both was determined by single crystal X-ray diffraction. Abstract : Two novel rhenium(i ) phosphinine complexes [Re(CO)3 Cl(η 1 -C5 H4 ClP)2 ] (1 ) and [Re(CO)2 Cl(η 1 -C5 H4 ClP)3 ] (2 ) were synthesized and the molecular structure of both was determined by single crystal X-ray diffraction. In compound1 the two coordinated phosphinine ligands are arranged in a cis position, whereas compound2 with three phosphinine ligands crystallizes in a meridional structural motif. Density functional theory investigations were executed to examine the relative stabilities of both complexes1 and2 .